Overcoming obstacles - Satchidananda, Swami, 1914-2002. (Buckingham, Va. : Integral Yoga Publications, 2011)
?One?s whole life is an obstacle course. The more obstacles you overcome, the bigger the prize. If you avoid the obstacles, then there is no prize. Without those obstacles, you would never discover your capabilities. So instead of cursing the obstacles on your path, or the people who placed them there, try to find ways that will help you face them and overcome them. And when you do, a great joy will arise within you and you will bless the obstacles instead of cursing them.? This quote from ?Overcoming Obstacles? captures the flavor of total positive thinking with which Swami Satchidananda teaches us to approach life?s inevitable challenges and convert all to opportunities for victory, fun, fulfillment and joy. Full of practical and priceless guidance.
Keywords: Spiritual life; Yoga; Religious life -- Hinduism; SELF-HELP / Personal Growth / Happiness; RELIGION / Prayer; RELIGION / Sermons / General; Electronic books